The Effectiveness of Using Kahoot-Based Digital Media in Enhancing Children's Social-Emotional Skills - Andi Nur Maharani Islami; Nurul Jamiah Sidiq; Faradillah Rusliana; Delvhina Manga (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This research aims to assess the effectiveness of Kahoot-based digital media in enhancing the social-emotional abilities of early childhood children. Social-emotional abilities examined include emotional recognition and regulation, cooperative skills, empathy development, and positive social relationship formation. The study employed a quantitative approach using a quasi-experimental design with pre-test and post-test measurements. The research was conducted at TK Aulia Rahma in Takalar, involving 16 children aged 5-6 years from Group B, divided into two groups: the experimental group (8 children) who received learning through Kahoot digital media, and the control group (8 children) who participated in conventional learning methods. Data collection utilized structured observation sheets and social-emotional assessment tools validated by experts. Data analysis employed the Wilcoxon Signed Rank Test to examine the significance of differences between pre-test and post-test results. The findings revealed significant improvements in the experimental group's social-emotional abilities (p = 0.011 < 0.05), with 62.5% of children achieving the "Very Good" category compared to only 12.5% in the control group. Children exposed to Kahoot demonstrated superior progress in teamwork, peer communication, emotional regulation, and empathy skills. These results indicate that Kahoot, with its interactive and gamified features, can effectively support the development of social-emotional skills in young children. The study recommends that educators integrate digital tools like Kahoot in early childhood classrooms to facilitate enjoyable learning experiences that promote emotional awareness and positive social interactions.